Demonstration system of pumped heat energy storage (PHES) and its round-trip efficiency. (1st March 2023) - Ameen, Muhammad Tahir; Ma, Zhiwei; Smallbone, Andrew; Norman, Rose; Roskilly, Anthony Paul
Highlights: World's first grid-scale PHES demonstrator system has been described. Performance of a novel heat pump/engine has been tested and losses are quantified. Round-trip efficiency of the system has been identified numerically. Round-trip efficiency is within a range of 70–80 % for single storage cycle. Periodic operation can yield a steady global round-trip efficiency of about 73 %. Abstract: Among the known energy storage technologies aiming to increase the efficiency and stability of power grids, Pumped Heat Energy Storage (PHES) is considered by many as a promising candidate because of its flexibility, potential for scale-up and low cost per energy storage unit. Whilst there are numerous demonstration systems under development, as it stands the only PHES demonstration system to be realised at scale is located in Hampshire, UK. This paper aims to present the results and analysis obtained from its commissioning and testing as part of an on-going study. The system was designed to offer a nominal power size of 150 kWe and energy storage capacity of 600 kWhe for an 8-hour storage cycle. This work presents evidence of the system Round-trip efficiency (RTE), which is considered as a fundamental performance metric for large-scale energy storage technologies. Recorded Pressure-Volume (P-V) measurements from recent heat pump/engine testing at part-load offers useful insight in terms of overall performance. Models are also developed to simulate the system to finally predict the performance at full-load conditions. The system and principle of operation are described first, followed by mathematical modelling outlining heat transfer mechanism and associated key losses involved in thermodynamic processes within components, and finally results are presented and compared at different operating conditions using different working gases. The results show good agreement with earlier studies, which indicate that expected electricity-to-electricity RTE is quite comparable to other mature technologies such as Pumped Hydropower Storage and Compressed Air Energy Storage. The cyclic operation of the system is also discussed. One-off storage cycle results in lower RTEs compared to a load-levelling cyclic operation where the efficiency is significantly improved due to stable packed-bed behaviour and better utilisation after an initial transient state.